Strength level of elderly adults by manual and functional electromechanical dynamometer - Catalán-Dibene, Ernani Francesco; Cruz-Castruita, Rosa María; Zambrano-Ayala, Stephanie Denise; Flores-Cruz, Mariela; López García, Ricardo; García Verazuluce, Juan José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
To evaluate upper body strength through the arm flexion test methods, manual dynamometry and functional electromechanical dynamometer in independent older adults. Transectional study, in 32 older adults. Data collected with a manual dynamometer, arm flexion test and with the Dynasystem Functional Electromechanical dynamometer. The results with the arm flexion test showed the highest strength indices were between 65 and 69 years old (21.9%; f = 7), in manual dynamometry the men presented low strength (15.6%; f = 5) and in the DEMF -DYNASYSTEM the highest percentage was for 7 repetitions (21.3%).